Urgency of Boundary Maritime Management: Strategies to Prevent Conflicts - Wattimena, Josina Augustina Yvonne (Indonesian Journal of International Law, 2017)
The boundary of maritime between countries is a very important issue for coastal States as well as archipelagic countries such as Indonesia. Indonesia is adjacent to the sea with ten neighboring countries. Until now, Indonesia has not completely resolved the sea border issues with neighboring countries. This is due to the determination of the sea boundary is not easy, very closely with various considerations such as; Political, legal, strategic, historical, economic, environmental, geographical, geological and geomorphological. With the enactment of the 1982 Sea Law Convention as a new constitution for the regulation of the law of the sea, consequently Indonesian as an archipelago country undergoes many changes that directly or indirectly affect the determination of the territorial sea border, exclusive economic zone as well as the continental shelf with neighboring countries. However, the establishment of Indonesia›s maritime boundaries with neighboring countries should be speeded up in its settlement. The basis of the argument is that the frequent border conflicts do not seem to be very potential to threaten the principle of good neighborly life as it is acknowledged in international law. Therefore, government functions can be maximized through integrated marine management. The integration of the management undertaken will clarify and reinforce the certainty and jurisdiction of Indonesia. Given this certainty and jurisdiction it is of great advantage to dimentially access and manage biodiversity sources of marine biological phenomenon. This becomes an effective means of affirming the sovereignty and sovereign rights and legitimacy of the State.